ANALISA PENGARUH VISCOSITAS OLI DAN TEMPERATUR OLI TERHADAP PERFORMANCE SISTEM HIDROLIK - Utomo, Gatut Prijo; Shofi, M. Tijanus (MEKANIKA: Jurnal Teknik Mesin, 2015)
Viscosity of a liquid is one of the characteristics that determine the amount of fluid resistance to shearforce, the viscosity occurs mainly due to the interaction between the molecules of the fluid in the hydraulic system.This viscosity depends on temperature changes, therefore, use the proper oil viscosity especially those that do notchange much with temperature is needed once the hydraulic system in order to get a good performance. Thehydraulic system is a technology that utilizes liquid, usually oil, to perform an inline movement or rotation. Thissystem works on the principle of Pascal, ie if a liquid subjected to pressure, the pressure will propagate in alldirections with no increase or decrease its power. Hydraulic Trainner machine is a device that works usinghydraulic system applications , to move the tool cylinders using a fluid or oil of type SAE 10 , SAE 30 and so on .This thesis aims to analyze the influence of oil viscosity and oil temperature of the hydraulic system performanceand showed that oil SAE 30 turned out to have a better performance approximately 18 % of the oil SAE 30. It can beconcluded that for Trainner hydraulic machine is better to use oil SAE 10 oil than SAE 30 . Keyword : viscosity, temperature, hydraulic system, SAE 10 oil and SAE 30 oil.